2003
DOI: 10.1029/2003gl017496
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of thermal and aerosol effects on the cloud‐to‐ground lightning density and polarity over large urban areas of Southeastern Brazil

Abstract: [1] The Brazilian lightning detection network detected about 310,000 cloud-to-ground flashes over three large metropolitan areas in Southeastern Brazil during three summer seasons (from 2000 to 2002). It was observed an enhancement of 60-100% in the flash density over the urban areas compared to their surroundings. Conversely, a decrease of 7 -8% in the percentage of positive flashes was also observed. The spatial distribution of the flashes follows closely the shape of the São Paulo city heat island, thereby … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
93
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(111 citation statements)
references
References 13 publications
14
93
0
2
Order By: Relevance
“…After that, several recent studies (Orville et al, 2001;Soriano and Pablo, 2002;Steiger et al, 2002;Naccarato et. al., 2003) have confirmed this result.…”
Section: Introductionmentioning
confidence: 99%
“…After that, several recent studies (Orville et al, 2001;Soriano and Pablo, 2002;Steiger et al, 2002;Naccarato et. al., 2003) have confirmed this result.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies found evidence of thermal, aerosol, and geographic impact on CG lightning physical properties. Modification of lightning density and polarity happened over large urban areas of southeastern Brazil [Naccarato et al, 2003]. Aerosols played a major role in enhancement in lightning activity over two inland metropolitan cities of India [Lal and Pawar, 2011].…”
Section: Introductionmentioning
confidence: 99%
“…Third, also from Fig. 6a, a large spot (the region in white in the state of São Paulo) of high flash density can be seen, coincident with the location of the city of São Paulo, the largest city of the country with a population larger than 10 million people, suggesting that the urban activity is affecting the thunderstorm activity (Naccarato et al, 2003;Pinto et al, 2004;Farias et al, 2008;Bourscheidt et al, 2012). The effects of orography and urban area are not evident in the low-resolution data in Figs.…”
Section: Resultsmentioning
confidence: 86%